Experiences of using artificial intelligence technologies in teaching the Arabic language - Toshtemirova , Shohista; Gafforov , Umarali (The Lingua Spectrum, 2025)
This article explores the use of artificial intelligence (AI) technologies in teaching the Arabic language. It analyzes AI-based tools such as chatbots, voice assistants, translation systems, and interactive learning platforms, focusing on their effectiveness in language acquisition. The study examines international and local practices of integrating AI into Arabic language instruction and assesses their applicability within the Uzbek educational system. The paper provides practical recommendations for utilizing AI to create a more personalized and interactive approach to learning Arabic, helping learners overcome linguistic challenges in a modern, tech-driven environment.